Hyaluronan-based heparin-incorporated hydrogels for generation of axially vascularized bioartificial bone tissues: In vitro and in vivo evaluation in a PLDLLA-TCP-PCL-composite system - Rath, S.N. (2014)
10.1007/s10856-011-4300-0